2019
DOI: 10.1007/s00784-019-03169-4
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory changes in Chinese patients after coronectomy vs. total extraction of mandibular third molar: a prospective study

Abstract: Objectives This study aimed to quantitatively compare the somatosensory function changes of inferior alveolar nerve (IAN) after mandibular third molar extraction with a surgery protocol of coronectomy, as opposed to the conventional method. Materials and methods Patients with a lower third molar directly contacting IAN were recruited and assigned either to a test group (coronectomy group) or a control group (conventional extraction). A standardized quantitative sensory testing (QST) battery was performed for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 51 publications
(167 reference statements)
1
26
0
3
Order By: Relevance
“…Accordingly, 44 full-text articles were assessed for eligibility, and 37 were excluded (Figure 1). Only 7 studies fulfilled the inclusion criteria for the quality synthesis: 3 RCTs [16][17][18] and 4 CCTs [5,15,19,20] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, 44 full-text articles were assessed for eligibility, and 37 were excluded (Figure 1). Only 7 studies fulfilled the inclusion criteria for the quality synthesis: 3 RCTs [16][17][18] and 4 CCTs [5,15,19,20] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…All studies considered a control group. Six studies monitored both sexes [5,[16][17][18][19][20]. e secondary outcomes including numbers and percentages of patients, teeth, incidence of pain, infection, alveolar osteitis, failure, and other variables are available in Table 3.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…First, a control group (total extraction of the M3M) was not included. The reason was because coronectomy is widely accepted as an effective alternative to prevent IAN injury [2]. Also, our ethics committee suggested that random grouping might not suitable in our study.…”
Section: Discussionmentioning
confidence: 98%
“…This is a single arm and single-blinded study. It is also part of an ongoing study on the long-term changes in the M3M after coronectomy [2]. Ethical approval of the study protocol was granted by the Biomedical Ethics Committee of Peking University Hospital of Stomatology (PKUSSIRB-201736080) in Beijing, China.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation